The Impact of Urbanization on Social Inequality: Evidence from Jakarta Metropolitan Area - Kurniawan, Dedy (Generasi Sains Indonesia, 2025)
Urbanization stands as a defining global trend of the 21st century, offering both prosperity and disparity for metropolitan regions. The Jakarta Metropolitan Area (Jabodetabek), home to over 30 million residents, exemplifies rapid urban growth in Southeast Asia. While economic expansion and infrastructural progress have advanced, deep social inequalities persist in housing, employment, education, health, and environmental security. Using a mixed-methods approach, this study integrates quantitative data from Statistics Indonesia, institutional reports, and GIS mapping with qualitative insights from interviews, focus group discussions, and field observations. The findings reveal entrenched structural inequalities. Migration flows dominated by low-skilled workers increase labor precarity, while 30% of households remain in informal settlements lacking adequate services. Income disparities between formal and informal sectors persist, and access to education and healthcare remains stratified by class. Moreover, modernization projects often displace vulnerable populations, worsening environmental risks for the poor. Ultimately, Jakarta’s urbanization functions as both an engine of modernization and a generator of inequality. Addressing these challenges demands inclusive urban governance that emphasizes equitable housing, sustainable planning, and social justice to ensure balanced development and fair distribution of urban prosperity across all social strata.